PEMBINAAN KARAKTER SISWA MELALUI KEGIATAN KEPRAMUKAAN DI SMP RIYADLUL JANNAH CISEENG – BOGOR - Ramadhan, Syahrul (Inspiratif Pendidikan, 2021)
This study aims to determine the effort of scout activities in developing students' character at SMP Riyadlul Jannah Ciseeng Junior High School - Bogor in academic year 2020/2021. The method used in this study is descriptive qualitative with research data sources from the results of observation scout activities directly, and interview that are delivered to 2 coaches and 3 students to obtain valid data about students' character building through scout activities at Riyadlul Jannah Junior High School, Ciseeng-Bogor. The results showed that scout activities at Riyadlul Jannah Junior High School are going quite well, scout activities contained the principle of learning by doing (learning by doing), and effort of scout activities in developing students' character at Riyadlul Jannah Junior High School Ciseeng-Bogor is included in the good category and succeeded in developing discipline, religious and creative character. Thus, this proves that scout activities are effective in building students' character at Riyadlul Jannah Ciseeng-Bogor Junior High School in academic year 2020-2021.